The extent and character of communication nurses with the parents of hospitalized child - Marć, Małgorzata (European Journal of Clinical and Experimental Medicine, 2005)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Communication is a basic of all activities undertaken by the nurse for the subject of care. The communication performed by the nurse is specially important in nursing a little child hospitalized on the ward. In that situation eliciting different data necessary for nursing purposed and care in its wide aspect is possible due to bilateral communication between the nurse and child’s parents. The aim of the paper is to present the extent and character of communication between pediatric nurse and child’s parents hospitalized in the pediatric ward. Two research group were included in the study: the parents (104 persons) and the nurses (109 persons) from pediatric ward in which the hospitalized children were staying. The research methods used were: survey, competent’s judge, statistic methods. The results indicate a broad extent of information mutually expected and received by the parents and nurses. The parents must be emphasized that they supplied expect complete answers by she nurse. The extent and character of information to be provided by parents is necessary for the nurse to execute nursing care and indirectly to treat the child.